FAKTOR DEMOGRAFI DAN PERSEPSI INDIVIDU DALAM MENENTUKAN JENIS INVESTASI UNTUK MASA PENSIUN - Naomi, Prima (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2018)
This study aimed to understand the relations among demographic factors, individuals’ perceptions and the type of retirement investment. Subjects were labor forces who work in Jakarta. We used 311 respondents. he method used is descriptive method, cross-tab and chi-square test. Most of the respondents chose to retire under 60 years of age, not expecting to get the cost of living from the child during retirement. While retiring most still hope to be able to perform activities as usual by doing activities of gardening, breeding and other productive activities. The most worrying thing is health problems, and followed by finances during retirement, child's condition, financial condition to be inherited, dependence on children, and social relationships. Most respondents have prepared investments to face retirement. The most interested type of investment respectively are: savings, property, gold, business, pension program. The least attractive type of investment is bonds. The results showed that some demographic factors (age, education level, marital status and occupation type and marital status) were significantly related to the perception of individuals facing retirement. Only the level of education and the type of work that is significantly related to the type of pension investment. Meanwhile, there is no significant relationship between individual perceptions and types of pension fund investments.